Refrigerating material, preparation method and refrigerator
By introducing austenite and nano-precipitation phases into NixTi100-x materials, the superelastic temperature zone is broadened, and the problem of the adiabatic temperature of NiTi shape memory alloy is solved, and superelastic refrigeration in a wide temperature domain is achieved Effect, suitable for a variety of refrigeration equipment.
Patent Information
- Application Number
- CN202411217680.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-07
AI Technical Summary
The existing NiTi shape memory alloy has a small adiabatic temperature change and a narrow operating temperature zone, which limits the application range of elastic and thermal refrigeration technology and cannot meet the refrigeration needs of refrigerators, freezers and high-temperature heat pumps.
Develop a NixTi100-x refrigeration material containing austenite (B2) phase and nano-precipitation phase. The superelastic temperature zone is broadened by nano-precipitation phase and supersaturated Ni to achieve wide temperature domain superelasticity, and the stress-induced phase is used. Change the latent heat to release the heat and refrigerate.
It has achieved super elasticity in a wide temperature range of 203K to 503K, with adiabatic temperature drop value up to 5K~33.6K, and a temperature span of 200K and 110K, which significantly improves the high-temperature yield strength and anti-functional decay ability of the material. It is suitable for refrigerators , freezer, air conditioner and heat pump equipment.
Smart Images

Figure CN119265452A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of materials, and in particular relates to a refrigeration material, a preparation method and a refrigerator. Background Art
[0002] Nowadays, refrigeration and heating equipment such as air conditioners, refrigerators, freezers and high-temperature heat pumps have become necessities that can be seen everywhere in our daily lives and industrial production. While providing us with convenience, these devices not only consume a lot of energy, but also have a serious impact on the environment due to their vapor compression refrigeration method. According to statistics from relevant departments, in 2019, refrigeration alone consumed about 20% of the world's electricity and accounted for 7.8% of global greenhouse gas emissions. These figures are expected to continue to increase by 2050. This undoubtedly exacerbates the energy crisis and the risk of global warming, forcing us to find a new green and efficient refrigeration technology as soon as possible.
[0003] Among all the possible alternatives, the elastic-caloric (also known as spring-cage) refrigeration technology based on the latent heat of stress-induced martensitic phase transformation of shape memory alloys is a green, efficient, sustainable and easy-to-operate emerging solid-state refrigeration / heating method, which is expected to alleviate the energy crisis and environmental problems faced by mankind. Using this technology, different forms of refrigeration prototypes have been developed based on NiTi shape memory alloys; by increasing the loading frequency and heat transfer efficiency and adopting methods such as series active heat recovery, the first new elastic-caloric refrigeration prototype can achieve a cooling power of 260W and a cooling temperature span (the difference between heat output and cold output) of 50.6K (from 277.1K to 327.7K). Although these indicators are encouraging, they are still smaller than the refrigeration capacity (kilowatt level) and temperature span (at least covering the temperature range between 233K and 453K) that can be achieved by traditional vapor compression cycles. In terms of temperature span alone, the current refrigeration prototype can only be used as an air conditioner (289K to 303K), and cannot be used to make refrigerators / freezers (233K to 258K) and high-temperature heat pumps (313K to 453K). The main reason for this dilemma is that the current commercial NiTi shape memory alloy has a smaller adiabatic temperature change (4-15K - at room temperature) than traditional vapor compression refrigerants, a narrower operating temperature range (only 60-70K) and is concentrated near room temperature. Limited by the above-mentioned characteristics of the material, the current prototype can only use multi-stage refrigeration or active heat recovery to obtain a slightly larger cooling / heating temperature span, which greatly limits the application scope of elastic caloric refrigeration. Therefore, in order to meet the needs of elastic caloric refrigeration, it is urgent to develop a new NiTi refrigerant with a wide temperature range and large elastic heat (large adiabatic temperature change). Summary of the invention
[0004] The present invention provides a refrigeration material, wherein the refrigeration material is Ni x Ti 100-x, x is 50.6-58.0 (i.e., the atomic weight of Ni accounts for 50.6%-58.0%), wherein the refrigeration material Ni x Ti 100-x Including: austenite (B2) phase and nano-precipitation phase. The nano-precipitation phase and supersaturated Ni are used to expand the upper and lower limits of its superelastic temperature range, respectively, to achieve wide temperature range superelasticity. In its superelastic temperature range, stress-induced Phase changes release (when loaded) and absorb (when unloaded) latent heat, thereby achieving heating and cooling.
[0005] Preferably, x is 51.0-53.0, that is, the atomic weight of Ni in the refrigerant material accounts for 51.0%-53.0%, wherein the volume fraction of austenite (B2 phase) at room temperature is 88%-70%, and the average particle size is 10-500 μm, preferably 100-300 μm. More preferably, x is 51.3-51.5, because the content of austenite is sufficient and is micron-sized coarse grains, when an external force is applied to cause austenite to undergo phase change, the refrigerant can generate a large latent heat.
[0006] Specifically, the nano-precipitated phase can be Ti3Ni4, TiNi3 or Ti2Ni3, and its volume fraction is 10%-30%, and the average particle size of the nano-precipitated phase is 1-50nm, and the average spacing is 3-20nm. Preferably, the nano-precipitated phase is lens-shaped Ti3Ni4, and the volume fraction is 13%-14%, and its average major axis is 2-18nm, the average minor axis is 2-9nm, and the average spacing is 6-10nm, which is coherent with the austenite phase matrix. Ultrafine nano-precipitated phase is uniformly dispersed in the austenite matrix, which can effectively strengthen the matrix, improve its critical plastic flow stress, and can effectively hinder the dislocation movement of the material in the cyclic phase transformation process, and improve its resistance to functional degradation.
[0007] Since the matrix is nickel-rich, anti-site defects are easily formed, which makes the martensitic phase transformation induced by the temperature of the nickel-rich NiTi refrigerant ( Phase transition) is significantly suppressed in the temperature range above 213K (or even lower temperature points). At this time, the material mainly undergoes diffusion in the above temperature range. Phase transition. Since the temperature-induced B2→B19′ phase transition is significantly suppressed, the material still contains B2 phase and R phase at temperatures as low as 213K, and stress-induced Phase change, so it can still cool and heat at temperatures as low as 213K.
[0008] Due to the strengthening effect of the nano-precipitated phase, the high-temperature yield strength of the matrix is significantly increased, so that the material can still undergo stress-induced martensitic phase transformation at very high temperatures without plastic slip, thus ensuring that the material can still be used for cooling and heating at very high temperatures (up to 503K).
[0009] A method for preparing a refrigeration material, comprising:
[0010] Ni and Ti are mixed in a molar ratio of (50.6-58):(49.4-42) to prepare an alloy;
[0011] The alloy is placed at a temperature of 1173-1323K for 12-48h for homogenization and then water quenched;
[0012] The water-quenched alloy is placed at a temperature of 573-973K for 5-300min aging treatment to obtain the refrigeration material Ni x Ti 100-x .
[0013] In the process of preparing the alloy, any method of arc melting, induction melting, and suspension melting (including suction casting, etc.) can be adopted. Ni and Ti can be selected from raw materials such as powder, granules, sheets, plates, ingots, etc., and the formed alloy can also be made into materials in the above forms (powder, granules, wires, sheets, plates, ingots, rods and tubes, etc.), which are not limited here.
[0014] Further, the prepared alloy is placed at a temperature of 1323-1473K and subjected to hot isostatic pressing treatment at a hydrostatic pressure of 100-300MPa for 1-10h, and then cooled in the furnace.
[0015] Preferably, the temperature of hot isostatic pressing is 1373-1423K, the time is 3-8h, and the hydrostatic pressure is 150-300MPa. By hot isostatic pressing the alloy, the holes generated during the alloy preparation process can be reduced, which helps to improve the fatigue resistance of the refrigerant during the phase change of the refrigeration cycle and improve its service life.
[0016] Preferably, at a temperature of 1223-1273K, a homogenization treatment of 14-24h is carried out. Under this temperature range, the alloy is homogenized and solution treated, so that each component can not only be diffused rapidly inside the material to achieve a homogenized effect, but also the unfavorable precipitation phase formed in the early stage melting cooling process can be dissolved simultaneously. Subsequently, water quenching rapid annealing is utilized to further prevent the precipitation of nano phase. After the above-mentioned homogenization treatment, a clean, nano-precipitated phase and uniform NiTi alloy can be obtained, so that when subsequent aging treatment is performed, required nano-precipitated phase is formed.
[0017] Further, the preferred aging treatment temperature is 623-873K, and the time is 5-50min. Aging treatment within the preferred temperature range can obtain a Ti3Ni4 nano-precipitate phase with a major axis of 2-18nm, a minor axis of 2-9nm, and a spacing of 6-10nm, and an austenite phase with a particle size of 100-300μm. At this time, the volume fraction of the Ti3Ni4 nano-precipitate phase is 13%-14%, which is uniformly dispersed in the austenite matrix, which can significantly strengthen the matrix and improve its functional stability.
[0018] The wide temperature range elastic refrigeration material can be applied to refrigerators, freezers, air conditioners, heat pumps and other refrigeration and heating equipment, without limitation herein.
[0019] The present invention uses NiTi alloy material rich in Ni (Ni atomic weight accounts for 50.6%-58.0%) for refrigeration, wherein the supersaturated Ni can effectively reduce the phase transition temperature and broaden the lower limit of the superelastic temperature zone, while the nano-precipitated phase can strengthen the austenite coarse grains (increase its high temperature yield strength), improve the upper limit of the material superelastic temperature zone, and make the alloy material have superelasticity at least in the temperature range of 203K to 503K (a total temperature span of 300K); thanks to the coarse grains The large latent heat generated by phase change can produce a temperature change of 5K to 33.6K during adiabatic compression deformation (the size of which depends on the ambient temperature); the temperature spans of adiabatic temperature drop amplitudes ≥10K and ≥20K can reach 200K and 110K respectively, which can achieve cooling and heating in a wide temperature range. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0021] Figure 1 This is a schematic diagram of the morphology of the refrigeration material prepared in Example 1 of the present application;
[0022] Figure 2 This is a microstructure test diagram of the refrigeration material prepared in Example 1 of the present application;
[0023] Figure 3 This is a DSC (heat flow) curve of the refrigerant material prepared in Example 1 of the present application;
[0024] Figure 4 This is the in-situ variable temperature XRD (X-ray diffraction) spectrum of the refrigeration material prepared in Example 1 of the present application;
[0025] Figure 5 This is a temperature-dependent compressive stress-strain curve of the refrigerant material prepared in Example 1 of the present application;
[0026] Figure 6 This is a diagram of adiabatic temperature drop of the temperature and stress dependence of the refrigeration material prepared in Example 1 of the present application;
[0027] Figure 7 The cyclic compression stress-strain curves at different temperatures of the refrigerant material prepared in Example 1 of the present application and the temperature oscillation diagram generated synchronously therewith. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0029] Example 1
[0030] (1) Ni and Ti particles with a purity of 99.99% (size ) were mixed in a molar ratio of 51.5:48.5, placed in a vacuum arc melting furnace, and melted into an alloy under an argon atmosphere; in order to allow the gas in the material to fully escape, the material was melted at a low current of 150A during the initial melting, and then melted at a maximum current of 240A. In order to ensure the uniformity of the alloy composition, the entire melting process was subjected to 5 upside-down remelting;
[0031] (2) placing the alloy at a temperature of 1323K and a hydrostatic pressure of 150MPa for 5h and then cooling it in the furnace;
[0032] (3) The cooled alloy was homogenized at 1173 K for 10 h and then water quenched;
[0033] (4) The homogenized ingot was cut into small square columns with a size of 2.5 mm × 2.5 mm × 5 mm, and placed in a heat treatment furnace. The temperature was raised from 723 K to 773 K at a rate of 5 K / min for aging treatment for 200 min, and then immediately water quenched to obtain a high-nickel NiTi refrigerant that can be used for wide temperature range elastic caloric refrigeration / pump heat.
[0034] The equipment used in the preparation process and the names and models of the testing instruments used on the refrigeration materials are as follows:
[0035] EBSD, electron backscatter diffraction, model: MIRA3LMH;
[0036] TEM, transmission electron microscope, model: JEM2010;
[0037] HRTEM, high-resolution transmission electron microscope, model: JEM2010;
[0038] DSC, differential scanning calorimeter, model: Netzsch DSC-214;
[0039] XRD, X-ray diffractometer, model: Rigaku Smartlab;
[0040] High and low temperature static compression testing machine, model: Instron 5969;
[0041] Low temperature MTS fatigue testing machine, model: Landmark 370.10.
[0042] Figure 1 The NiTi refrigerant alloy ingot prepared in Example 1 has a microstructure as shown in FIG. Figure 2 As shown. Among them, Figure 2 (a), (b) and (c) are EBSD, TEM and HRTEM images respectively. Figure 2 It can be seen that the microstructure of the refrigerant is composed of micron-sized coarse-grained austenite (B2 phase, see Figure 2 (a), (1-i) and (1-ii)) and ultra-dense and ultra-fine nano-precipitates (see Figure 2 The average grain size of the B2 phase is 281 μm (see Figure 2 (a) and (d)), the average long axis of the precipitated phase is 8.7nm, the average short axis is 4.7nm, and the average spacing is 8.2nm (see Figure 2 (c)).
[0043] The refrigerant prepared in Example 1 was subjected to DSC and XRD tests. Figure 3 and 4 The martensitic transformation behavior induced by the refrigerant temperature was characterized. Figure 3 and Figure 4 It can be seen that the refrigerant can only diffusely induce partial temperature-induced Phase change; The phase transition is significantly suppressed.
[0044] The refrigerant in Example 1 was subjected to high and low temperature compression test and adiabatic temperature drop characterization using an Instron 5969 high and low temperature static compression tester and a thermocouple. The results are as follows: Figure 5 and Figure 6 As shown. Figure 5It can be seen that the refrigerant can have superelasticity in the temperature window of 213K to 503K (nearly 300K temperature span) without exceeding its yield strength. Figure 6 It can be seen that the refrigerant can produce a temperature drop of -5K to -33.6K at 203K to 503K; the temperature spans with adiabatic temperature drop amplitudes ≥10K and ≥20K can reach 200K and 110K respectively.
[0045] The functional stability test of the refrigerant prepared in Example 1 was carried out using a low-temperature MTS fatigue tester: cyclic compression stress-strain tests were carried out at different temperatures, and the temperature oscillations generated synchronously were recorded using a thermocouple (N is the number of cycles, and the loading frequency is 10 Hz). The results are shown in FIG. Figure 7 As shown. Figure 7 It can be seen that after tens of thousands of cycles, the residual strain of the refrigerant can be basically ignored, and the adiabatic temperature change remains almost unchanged, showing excellent cycle stability.
[0046] The above content is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application are included in the protection scope of the present application.
Claims
1. A refrigeration material, characterized in that: The refrigeration material is Ni x Ti 100-x , x is 50.6-58.0, wherein the refrigeration material Ni x Ti 100-x Includes: austenite phase and nano-precipitation phase.
2. The refrigerant material according to claim 1, characterized in that: x is 51.0-53.
0.
3. The refrigerant material according to claim 1, characterized in that: The volume fraction of the nano-precipitated phase is 10%-30%, and the nano-precipitated phase is Ti3Ni4, TiNi3 or Ti2Ni3.
4. The refrigerant material according to claim 1, characterized in that: The average grain size of the austenite phase is 10-500 μm.
5. The refrigerant material according to claim 1 or 3, characterized in that: The average particle size of the nano-precipitated phase is 1-50 nm, and the spacing is 3-20 nm.
6. A method for preparing a refrigerant material according to any one of claims 1 to 5, characterized in that: include: Ni and Ti are mixed in a molar ratio of (50.6-58.0):(49.4-42.0) to prepare an alloy; The alloy is placed at a temperature of 1173-1323K for 12-48h for homogenization and then water quenched; The water-quenched alloy is placed at a temperature of 573-973K for 5-300min aging treatment to obtain the refrigeration material Ni x Ti 100-x .
7. The preparation method according to claim 6, characterized in that: Also includes: The prepared alloy is placed at a temperature of 1323-1473K and subjected to hot isostatic pressing treatment at a hydrostatic pressure of 100-300MPa for 1-10h, and is cooled along with the furnace.
8. The preparation method according to claim 6, characterized in that: The temperature of the aging treatment is 623-873K, and the time is 5-300min.
9. The preparation method according to claim 6, characterized in that: The molar ratio of Ni to Ti is: (51.0-53.0): (49.0-47.0)。 10. A wide temperature range elastic caloric refrigerator, characterized in that: include: The refrigerant material according to claims 1 to 5; Or, a refrigerant material prepared by the preparation method according to claims 6 to 9.
Citation Information
Cited By
Refrigeration material, preparation method, and cooler
WO2026046040A1